Dysfunctional β-cell autophagy induces β-cell stress and enhances islet immunogenicity - Austin, Matthew C.; Muralidharan, Charanya; Roy, Saptarshi; Crowder, Justin J.; Piganelli, Jon D.; Linnemann, Amelia K. (Frontiers in Immunology, 2025)
BackgroundType 1 Diabetes (T1D) is caused by a combination of genetic and environmental factors that trigger autoimmune-mediated destruction of pancreatic β-cells. Defects in β-cell stress response pathways such as autophagy may play an important role in activating and/or exacerbating the immune response in disease development. Previously, we discovered that β-cell autophagy is impaired prior to the onset of T1D, implicating this pathway in T1D pathogenesis.AimsTo assess the role of autophagy in β-cell health and survival, and whether defects in autophagy render islets more immunogenic.MethodsWe knocked out the critical autophagy enzyme, ATG7, in the β-cells of mice (ATG7Δβ-cell) then monitored blood glucose, performed glucose tolerance tests, and evaluated bulk islet mRNA and protein. We also assessed MHC-I expression and presence of CD45+ immune cells in ATG7Δβ-cell islets and evaluated how impaired autophagy affects EndoC-βH1 HLA-I expression under basal and IFNα stimulated conditions. Lastly, we co-cultured ATG7Δβ-cell islet cells with diabetogenic BDC2.5 helper T cells and evaluated T cell activation.ResultsWe found that all ATG7Δβ-cell mice developed diabetes between 11-15 weeks of age. Gene ontology analysis revealed a significant upregulation of pathways involved in inflammatory processes, response to ER stress, and the ER-associated degradation pathway. Interestingly, we also observed upregulation of proteins involved in MHC-I presentation, suggesting that defective β-cell autophagy may alter the immunopeptidome, or antigen repertoire, and enhance β-cell immune visibility. In support of this hypothesis, we observed increased MHC-I expression and CD45+ immune cells in ATG7Δβ-cell islets. We also demonstrate that HLA-I is upregulated in EndoC β-cells when autophagic degradation is inhibited. This effect was observed under both basal and IFNα stimulated conditions. Conversely, a stimulator of lysosome acidification/function, C381, decreased HLA-I expression. Lastly, we showed that in the presence of islet cells with defective autophagy, there is enhanced BDC2.5 T cell activation.ConclusionsOur findings demonstrate that β-cell autophagy is critical to cell survival/function. Defective β-cell autophagy induces ER stress, alters pathways of antigen production, and enhances MHC-I/HLA-I presentation to surveilling immune cells. Overall, our results suggest that defects in autophagy make β-cells more susceptible to immune attack and destruction.